2019
DOI: 10.1080/20013078.2019.1697124
|View full text |Cite
|
Sign up to set email alerts
|

Plasma mEV levels in Ghanain malaria patients with low parasitaemia are higher than those of healthy controls, raising the potential for parasite markers in mEVs as diagnostic targets

Abstract: Inal (2020) Plasma mEV levels in Ghanain malaria patients with low parasitaemia are higher than those of healthy controls, raising the potential for parasite markers in mEVs as diagnostic targets,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 84 publications
0
30
0
Order By: Relevance
“…Indeed, in teleost, it has been reported that changes in EV numbers and EV deimination protein and microRNA cargo can be a biomarker for environmental temperature factors [ 33 ] and, in response to other stressors, teleost plasma EVs have been found enriched with Hsp70 [ 46 ] and selected micro-RNAs [ 47 ]. In human parasitic disease, EV profiles can also be indicative of infection status [ 48 ]. Therefore, the characterisation of EVs across a wide range of taxa further highlights their potential for biomarker application or “EV-fingerprinting” for the assessment of animal health.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in teleost, it has been reported that changes in EV numbers and EV deimination protein and microRNA cargo can be a biomarker for environmental temperature factors [ 33 ] and, in response to other stressors, teleost plasma EVs have been found enriched with Hsp70 [ 46 ] and selected micro-RNAs [ 47 ]. In human parasitic disease, EV profiles can also be indicative of infection status [ 48 ]. Therefore, the characterisation of EVs across a wide range of taxa further highlights their potential for biomarker application or “EV-fingerprinting” for the assessment of animal health.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 ). We and others have previously shown that malaria parasites release EVs during their blood-stage to deliver cargo between them and to their host 18 23 . Specifically, the parasites deliver cargo to immune and endothelial host cells to promote their growth 6 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It is now clear that EVs and their cargo have potential as biomarkers. Their elevated numbers, notably endothelial-, platelet-and RBC-derived MVs, in the circulation of human patients with CM has already been proven in multiple studies [39,84,91] . The role of EVs as a biomarker in severe malaria is still in its infancy and in-depth multi-centre studies are still needed to ascertain their predictive value to improve rapid detection in bodily fluids.…”
Section: Extracellular Vesicle Cargo: Effector Biomarker or Both?mentioning
confidence: 97%